2022
DOI: 10.1002/adfm.202204692
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Vaccines Against SARS‐CoV‐2 Variants Delivered by Lipid Nanoparticles Based on Novel Ionizable Lipids

Abstract: SARS‐CoV‐2 variants are now still challenging all the approved vaccines, including mRNA vaccines. There is an urgent need to develop new generation mRNA vaccines with more powerful efficacy and better safety against SARS‐CoV‐2 variants. In this study, a new set of ionizable lipids named 4N4T are constructed and applied to form novel lipid nanoparticles called 4N4T‐LNPs. Leading 4N4T‐LNPs exhibit much higher mRNA translation efficiency than the approved SM‐102‐LNPs. To test the effectiveness of the novel delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…6 G, the elevated level of IgG in serum was observed when mice immunized with CMR-PLGA/p54 NVs. Alternatively, the ratio of IgG2a to IgG1 is a marker for Th1 and Th2 immune responses [ 52 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 G, the elevated level of IgG in serum was observed when mice immunized with CMR-PLGA/p54 NVs. Alternatively, the ratio of IgG2a to IgG1 is a marker for Th1 and Th2 immune responses [ 52 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). The formulation of LNPs containing IC8 had been optimized in our previous study, so as to show good transfection in mRNA delivery ( 32 ). Therefore, we prepared IC8 LNPs loading luciferase mRNA (IC8@Luc) and IC8/Mn LNPs loading Luc mRNA (IC8/Mn@Luc) (containing a different mass ratio of Mn to mRNA) using a microfluidic device ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that the ionizable lipid in LNPs notably influenced the mRNA expression. The ionizable lipids with multiple tertiary amino nitrogen atoms, compared to the ones with one nitrogen atom like mRNA-1273, could remarkably enhance the immunogenicity of mRNA vaccines ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lipid nanoparticles (LNPs) have been shown to enable efficient and safe mRNA delivery, and have been successfully used to treat SARS-CoV-2 infections through the delivery of mRNA (such as SM-102 and ALC-0315 LNPs for mRNA-1273 and BNT162b2) 22 , 27 . Ionizable lipids, one of the key components of LNPs, are critical to enhancing the delivery efficiency and therapeutic efficacy of mRNA vaccines 27 , 28 , 29 , 30 . Ionized lipids provide a positive charge to ensure maximum encapsulation of negatively charged mRNAs into LNPs through electrostatic interactions and help mRNAs cross cellular barriers 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The rational design of ionizable lipids has great potential to initiate more potently protective immunity of mRNA-LNP vaccines 31 , 32 . We designed a new set of multi-charged ionizable lipids (MIC1-MIC6) and found significant increases in the transfection and expression efficiency of mRNA 30 .…”
Section: Introductionmentioning
confidence: 99%